Development of simulated human milk ultrafiltrate (SHMUF) for analysis of native particles in human milk - Johanna R. de Wolf; Jos M. J. Paulusse; Nienke Bosschaart (Scientific Reports)
Abstract Research into human milk often involves freezing, thawing and diluting. However, these steps influence the integrity of native milk particles, such as casein micelles (CMs) and extracellular vesicles (EVs). Correct sample preparation is vital for research into these particles, but validated protocols are scarce in the literature. Here, we design, synthesise and evaluate a novel medium for dilution: simulated human milk ultrafiltrate (SHMUF), aimed to preserve particle integrity. We evaluate the stability of fresh and frozen/thawed human milk in SHMUF, bovine simulated milk ultrafiltrate (SMUF), phosphate buffered saline (PBS) and demineralised water through changes in light scattering in optical transmission. Light scattering by human milk diluted with SHMUF remains stable for 10 h, whereas substantial changes are observed for milk samples diluted with the other media. Likewise, freezing and thawing cause changes in light scattering. We conclude that SHMUF most optimally preserves native particles, and that – ideally – freezing and thawing should be avoided.